Efficacy and safety of TACE combined with lenvatinib and PD-1 Inhibitor in intermediate-stage HCC exceeding the up-7 criteria: a retrospective cohort study - Xue, Miao; Wu, Yanqin; Tang, Yiyang; Huang, Kun; Liu, Haikuan; Zhu, Bowen; Wen, Jie; Zhao, Yue; Zhang, Guixiong; Liu, Hang; Fan, Wenzhe; Li, Jiaping (Frontiers in Immunology, 2025)
PurposeThis study aimed to assess the efficacy and safety of combining transarterial chemoembolization (TACE) with lenvatinib and a PD-1 inhibitor (TACE+LEN+PD-1) compared to TACE combined with lenvatinib alone (TACE+LEN) in intermediate-stage hepatocellular carcinoma (HCC) patients exceeding the up-to-7 criteriaMaterials and methodsData from 115 patients with intermediate-stage HCC exceeding the up-to-7 criteria, treated between January 2015 and December 2023, were prospectively collected and retrospectively analyzed. Key clinical outcomes, including overall survival (OS), progression-free survival (PFS), tumor response rates based on modified Response Evaluation Criteria in Solid Tumors (mRECIST), and adverse events (AEs), were evaluated and compared between the two treatment groups. Univariate and multivariate analyses were performed to identify factors affecting OS and PFS.ResultsAmong the patients, 35 received TACE+LEN+PD-1, and 80 underwent TACE+LEN. The TACE+LEN+PD-1 group achieved a longer median PFS (10.0 months vs. 5.7 months; P=0.002) and a median OS of 21.0 months, compared to 16.2 months in the TACE+LEN group, though the OS difference was not statistically significant (P=0.096). Progression to macrovascular invasion (MVI) or extrahepatic spread (EHS) was delayed in the TACE+LEN+PD-1 group compared to the TACE+LEN group (12.0 months vs. 7.5 months; P=0.007). Multivariate analysis identified treatment modality and tumor burden score (TBS) as independent prognostic factors for OS and PFS. Subgroup analyses showed that patients with an Eastern Cooperative Oncology Group (ECOG) performance status (PS) of 0 or HBV positivity derived greater benefits from TACE+LEN+PD-1, while those with high TBS or a Child-Pugh score of 7 did not show similar advantages. The rates and severity of AEs were comparable between groups (any grade: 88.6% vs. 91.3%, P=0.733; grade 3 or 4: 48.6% vs. 42.5%, P=0.546).ConclusionTACE+LEN+PD-1 significantly improved PFS, particularly by delaying progression to MVI or EHS after the first TACE session in intermediate-stage HCC patients exceeding the up-to-7 criteria, compared to TACE+LEN. Subgroup analysis indicated superior survival benefits for patients with a PS of 0 or HBV positivity, but not in those with high TBS or a Child-Pugh score of 7. The safety profile of TACE+LEN+PD-1 was comparable to TACE+LEN. However, the OS benefit between the two groups was not statistically significant.